Identifikasi Penggunaan Kata Non Baku Pada Surat Masuk Di Kantor Pertanahan Kab. Probolinggo - Ahnaf, Fatih Holis; Za'ada, Aprilia Coriyatus; Naqiah, Nuril Kamilatin; Rizki, Vita Vitriati (Universitas Negeri Padang, 2024)
ABSTRACTThis article discusses the identification of the use of non-standard words in correspondence at the Probolinggo district land office. This article contains the results of research related to non-standard words. We often find non-standard words in correspondence in the writing, where there are some writings that are still inaccurate or do not match the Indonesian spelling. This article uses a qualitative descriptive method approach with literature study. Data collection was carried out through literature study. Researchers involve the process of observation, interviews and documentation related to the research. The literature study is to look for a theory that is quite relevant, observations are carried out at the Kraksaan Land Office, Probolinggo Regency in order to get more detailed information, while the documentation itself is used as a source of data related to correspondence related to its writing. In accordance with this analysis, a system for writing incoming correspondence will be developed using language that matches the existing spelling. It is hoped that the results of this research will be able to provide a contribution in terms of increasing efficiency in the correspondence process.Keywords: words, literary studies, letters